A study on barrier-free campus: from perspective of disabled community: case study of University Malaya, Kuala Lumpur - Mohamed Osman, Mariana; Muhd Radzi, Fatimah Husna; M Bakri, Nurul Izzati; Ibrahim, Mansor (Elsevier, 2015)
Barrier free environment is vital to the disabled community in order to provide accessible facilities and environment, which promote independence, convenience and safety for all regardless of people ability to move. This paper discusses about the provision of facilities for disabled people and barrier-free design facilities in University Malaya (UM) focused on the six different selected studied areas. Barrier-free design facilities derived from the universal design concept that allows designated facilities without any limitation towards the elderly, children, disabled people and able-bodied people. According to literature, many problems occurred related to the provision of barrier-free facilities which are distribution pattern did not comprehensive within the campus area, facilities did not well-maintained and vandalism by the able-bodied people. This research aimed to identify available barrier-free facilities in UM; recognize the issues and problems faced by the disabled community and to provide recommendations and measures to be taken in order to satisfy the needs of the disabled community. The study used the methods of assess audit checklist, observation, interviews and questionnaire survey. A structured audit checklist used in the study was to ascertain the current facilities provided in the campus area are following is to the Malaysian Standard Code of Practice (Malaysian Standard, SIRIM, 2003). A questionnaire survey distributed to the respondents and analyzed using Statistical Package for the Social Sciences (SPSS) in order to identify the level of satisfaction of the disabled users. Interviews with the management of University Malaya identified the problems faced by the University’s management in providing barrier free facilities. The identified issues were lack of maintenance of the current facilities; the facilities built not following the guidelines or Standards and the overall facilities provided by the university were not accessible to disabled people. Hence, this paper proposed several recommendations for future references and improvement on the barrier-free design facilities in higher learning institutions.